Uncovering Teachers’ Challenges in Teaching Qualitative Research: Basis for Innovation and Training - Torres, Joseph (Journal of Interdisciplinary Perspectives, 2024)
The purpose of this study is to uncover the challenges of teachers teaching qualitative research in North District, Tanjay City Division, for the school year 2023-2024. This study employed a phenomenological design to characterize and comprehend teachers' circumstances. The researcher used a qualified teacher to facilitate focus group discussion with the six participants following an interview guide to gather data and for reflexivity purposes. The FGD was conducted four times for data saturation purposes at one of the restaurants in Tanjay City since it was the participants’ choice and convenience. Moreover, purposive sampling was utilized by the researcher based on the selection criteria. Additionally, a consented audio recording proved to be helpful in accurately transcribing the participants' comments, which were subsequently subjected to thematic analysis. To do this, the researcher had to become familiar with the transcripts, create codes, group codes into themes, examine and clarify themes, and present results. The study revealed five themes: missed opportunities, diversity amidst challenges, management constraints, students’ attitudes towards research and resilience, and resourcefulness amidst challenges. This revealed that teachers’ lack of knowledge, training, irrelevant skills in the subject, students’ low comprehension skills, and lack of interest are the underlying challenges that teachers face in teaching qualitative research. However, despite these challenges, teachers demonstrated resilience and resourcefulness by finding ways to gain knowledge and practice that could help them deliver the subject. Consulting experienced teachers, sourcing out other references, localizing materials, and translating English to Cebuano, their mother tongue teachers helped them sustain the goal of their profession to teach. Thus, the results of this study will form the basis for innovation, training, and workshops for research teachers. This study recommends that Tanjay City Division strengthen any enhancement program that aims to capacitate the teachers in research. Moreover, future researchers can do instrumentation on thematic analysis to gauge the knowledge and skills of research teachers in analyzing qualitative data which will be the basis for innovation and future enhancement programs in research.